Extracellular Matrix in Synthetic Hydrogel‐Based Prostate Cancer Organoids Regulate Therapeutic Response to EZH2 and DRD2 Inhibitors. Issue 2 (14th November 2021) - Mosquera, Matthew J.; Kim, Sungwoong; Bareja, Rohan; Fang, Zhou; Cai, Shuangyi; Pan, Heng; Asad, Muhammad; Martin, Maria Laura; Sigouros, Michael; Rowdo, Florencia M.; Ackermann, Sarah; Capuano, Jared; et al.
Abstract: Following treatment with androgen receptor (AR) pathway inhibitors, ≈20% of prostate cancer patients progress by shedding their AR‐dependence. These tumors undergo epigenetic reprogramming turning castration‐resistant prostate cancer adenocarcinoma (CRPC‐Adeno) into neuroendocrine prostate cancer (CRPC‐NEPC). No targeted therapies are available for CRPC‐NEPCs, and there are minimal organoid models to discover new therapeutic targets against these aggressive tumors. Here, using a combination of patient tumor proteomics, RNA sequencing, spatial‐omics, and a synthetic hydrogel‐based organoid, putative extracellular matrix (ECM) cues that regulate the phenotypic, transcriptomic, and epigenetic underpinnings of CRPC‐NEPCs are defined. Short‐term culture in tumor‐expressed ECM differentially regulated DNA methylation and mobilized genes in CRPC‐NEPCs. The ECM type distinctly regulates the response to small‐molecule inhibitors of epigenetic targets and Dopamine Receptor D2 (DRD2), the latter being an understudied target in neuroendocrine tumors. In vivo patient‐derived xenograft in immunocompromised mice showed strong anti‐tumor response when treated with a DRD2 inhibitor. Finally, we demonstrate that therapeutic response in CRPC‐NEPCs under drug‐resistant ECM conditions can be overcome by first cellular reprogramming with epigenetic inhibitors, followed by DRD2 treatment. The synthetic organoids suggest the regulatory role of ECM in therapeutic response to targeted therapies in CRPC‐NEPCs and enable the discovery of therapies to overcome resistance. Abstract : Neuroendocrine prostate cancer is epigenetically transformed tumors for which no targeted therapies exist. Using a combination of transcriptomics, proteomics, spatial omics, and microscopy on patient biopsies, the extracellular matrix tumor microenvironment is defined. Informed by findings, synthetic hydrogel‐based prostate cancer organoids are developed to grow patient tumor cells under the defined microenvironment conditions, leading to the discovery of novel therapeutics.